Rectosigmoid resection morbidity in ovarian cancer cytoreductive surgery - Saeed Usmani, Afshan; Yasin, Iqra; Rehan Bin Asif,; Nazish Khalid,; Aamir Ali Syed, (Journal of the Pakistan Medical Association, 2023)
This case series evaluated morbidity following rectosigmoid resection during cytoreductive surgery for advanced ovarian cancer at the Shaukat Khanum Memorial Cancer Hospital, Lahore. The data of 20 female patients with complications corresponding to the Clavien-Dindo classification was included; the patients received treatment between January 2016 and January 2021. The mean age was 45.05± 13.11 years. Complications were observed in 3 (15.0%) cases, i.e., urinary complications in 2 (66.7%), and intra-abdominal abscess in 1 (33.3%) case. Clavien-Dindo classification grade II was noted in 2 (66.7%), while grade III-B in 1 (33.3%) case. Surgical risk factors were noted as appendectomy in 6 (66.7%) cases, bowel resection in 1 (11.1%), left colectomy in 1 (11.1%), sigmoid colectomy in 1 (11.1%), and stoma formation in 11 (55.0%) cases. In this reported case series, significant complications were observed in women undergoing rectosigmoid resection as cytoreductive surgery for advanced ovarian cancer.